Content of Radioactive Admixtures in Mineral Coal of Ukraine - Stepanov A.E.; Rublevsky N.T. (General Energy Institute of the National Academy of Sciences of Ukraine, 2000)
It was made an attempt to estimate the content of radioactive isotopes in coal extracted in Ukraine in 1990. It was shown there were more than hundred tons of radioactive materials in coal extracted on the level of hundreds billion tons. It demands serious learning the processes of their dispersion, accumulation in environment and influence on biosphere of Ukraine.